Sanitation law and policy in India : an introduction to basic instruments - Cullet, Philippe; Bhullar, Lovleen (New Delhi : Oxford University Press, 2016)
The past couple of decades have witnessed an increased interest in sanitation in India. In contrast to the policy perspectives on sanitation, however, there is a lack of knowledge about its legal dimensions. This book attempts to fill this gap by piecing together the provisions of the existing legal and policy instruments that address the different dimensions of sanitation in India. In the process, it highlights the importance, complexity and fragmented nature ofthese legal and policy frameworks.
Includes bibliographical references.
Specialized.
Description based on online resource; title from home page (viewed on December 17, 2015).
Keywords: Sanitation -- Law and legislation -- India; Sanitation -- Government policy -- India; Law